9(x+7)=5x-(6-x)

Simple and best practice solution for 9(x+7)=5x-(6-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x+7)=5x-(6-x) equation:



9(x+7)=5x-(6-x)
We move all terms to the left:
9(x+7)-(5x-(6-x))=0
We add all the numbers together, and all the variables
9(x+7)-(5x-(-1x+6))=0
We multiply parentheses
9x-(5x-(-1x+6))+63=0
We calculate terms in parentheses: -(5x-(-1x+6)), so:
5x-(-1x+6)
We get rid of parentheses
5x+1x-6
We add all the numbers together, and all the variables
6x-6
Back to the equation:
-(6x-6)
We get rid of parentheses
9x-6x+6+63=0
We add all the numbers together, and all the variables
3x+69=0
We move all terms containing x to the left, all other terms to the right
3x=-69
x=-69/3
x=-23

See similar equations:

| 2y-5=8y-25 | | 12x+4x+16=20-4x | | 10x=8x-35 | | 24-5x=-31 | | 24-5x=31 | | 10x+25=5(2x+12)+1 | | 15(2/3x+10)=15(x/5+36/5) | | 7x-8=3x+5+4x | | 9x-19=2(2x-7)-5+5x | | 5/12=16/x | | (4z+3)(5z)=96 | | k−16=233 | | s+6=30 | | (x+7)(x+3)=396 | | 3+9n=0 | | g+13=53 | | 5x+(-x)-1=-2x | | u+18=96 | | -12x^2-26x-60=0 | | 14s+5-3(3s-6)=5+6(s=3) | | 9+6s-3s+17=2s+18+3s | | 9+6s-3s+17=25+18+3s= | | Y=-4x+100 | | 2/3•w=30 | | y2–12y+11=0 | | 12y+48=180-8y-40 | | 2(x-3)-1=x+8 | | x+44=180-x | | 9x-3=3x+3 | | (36x-12)-5x=10 | | x-355+x+80-x=2425 | | x^2-5x-450=0 |

Equations solver categories